AI Platforms for Digital Servitization and Solution Delivery: Where ecosystem, production technology, and business model trajectories intersect to generate smart solutions - Vaillant, Yancy; Wamba, Samuel Fosso; Rabetino, Rodrigo (Elsevier, 2026)
The rapid advancement of digitalization and artificial intelligence (AI) is transforming the manufacturing landscape, creating turbulence and complexity that challenge established managerial frameworks. Many of the theoretical models that once guided production management now require revision to remain relevant in an AI-driven environment. This special issue on AI Platforms for Digital Servitization and Solution Delivery of the International Journal of Production Economics addresses this need by integrating research on three converging trajectories—platform ecosystems, digital servitization, and solution delivery—into a unified, programmatic theoretical framework. The editorial conceptualises AI platforms as key enablers that connect these domains, facilitating the development of comprehensive smart solutions through the alignment of business models, production technologies, and value ecosystems. Collectively, the studies contribute to a deeper understanding of how AI reshapes value creation and delivery in manufacturing contexts. This framework provides a foundation for future empirical validation and offers practical insights to guide managers in navigating the evolving realities of algorithmic-driven production systems.
Keywords: fi=Strateginen johtaminen|en=Strategic Management|